Digital Game-Based Learning Wordwall to Improve Vocabulary Mastery of Grade Eight Students at SMPN 2 Labobo - Nurhayati Ahdani; Mochtar Marhum; Zarkiani Hasyim; Afrillia Anggreni (MASI Mandiri Edukasi, 2026)
Rural EFL students at SMPN 2 Labobo face difficulties in mastering English vocabulary because the learning process is often boring and relies on traditional, teacher-centred methods. resulting in frequent word retention problems, inaccurate usage, and low motivation in learning English. Therefore, this research aimed to evaluate the effect of game-based learning using Wordwall on improving English vocabulary mastery of eighth-grade students at SMPN 2 Labobo. The research employed a quantitative pre-experimental design with a one-group pre-test and post-test approach, involving 19 students. The intervention consisted of six meetings using interactive Wordwall activities, including matching pairs, quizzes, word searches, sentence building, and categorisation, focusing on nouns, verbs, and adjectives in context. Vocabulary mastery was assessed via written tests evaluating grammatical accuracy, appropriate vocabulary use, and sentence clarity. Data from the pre-test and post-test were analysed using a paired-samples t-test. The results showed a significant improvement, with pre-test mean scores rising from 36.63 to 72.16 post-test, a gain of 35.53 points, and a paired t-test confirming statistical significance, t = -10.809, p = 0.000. These findings highlight that Wordwall's strategy is effective in enhancing engagement and retention in a rural school context, offering pedagogical implications for integrating digital tools in English as a Foreign Language (EFL) instruction.